Photoelectrochemical Cathodic Anti-corrosion of Copper by TiO2 Coating - แห้วเพ็ชร, ปิยพล; แซ่เฮง, ชนาพร; ทองมา, ภาวิณี; เงาตระการวิวัฒน์, ไพลิน (Engineering and Technology Horizons, 2019)
Photoelectrochemical cathodic protection of copper was achieved by TiO2 coating. The loss of electrons of copper under circumstances of corrosive gases affected by the concentration of corrosive gases in the rage of 2-10 ppm. The corrosive condition was severe at 10 ppm of sulfur oxide leading to the highest loss of electrons at 0.8602 μA/cm2. Moreover, effect of parameters for the preparation of TiO2 film coated on indium-tin oxide coated glass on photo-excited electrons generation under UV irradiation of 1 mW/cm2 were also investigated. The suitable composition of coating solution consisted of polyurethane 0.25 mL/ g TiO2. The TiO2 film at 0.35-μm thickness exhibited the highest photo-excited electrons generation at 7.1 μA/cm2. Furthermore, the copper rod coated with TiO2 film could prevent corrosion under 1 mW/cm2 UV irradiation in air consisting of corrosive gases 10 ppm. Comparing to bare copper rod, the copper rod coated with TiO2film could reduce the corrosion current to 79.5% and 82.5% under the dark and UV irradiation, respectively.